Закарпаття у відносинах між Чехословаччиною та Радянським Союзом у роки Другої світової війни. Радянсько-Чехословацький договір 29 червня 1945 року - Грін, О.О. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Проанализирован процесс развития дипломатических отношений между Чехословакией и Советским Союзом в годы Второй мировой войны, а также подписание 29 июля 1945 г. соответствующего договора между этими странами. Автор делает вывод о том, что альтернативы присоединения Закарпатской Украины к Советской Украине в тех конкретно-исторических условиях не существовало. The process of the development of diplomatic relations between Czechoslovakia and the Soviet Union in the World War II and the signing of the treaty between these countries on the 29th of July 1945 are analyzed in this article on the basis of scientific analysis of the international documents, archives data and monographs. The author makes the conclusion that there wasn't any other alternative of annexing of Transcarpathian Ukraine to the Soviet Ukraine at those specific historical conditions.